Liberating Oppressed Class, Community and Gender:Some Reflections - Tuladhar, Subarna Man (Administration and Management Review, 2009)
All indicators continue to show a greatly disadvantaged position of the oppressed class, community and gender in the Nepalese society. Many social activists believe that institutionalized discrimination between men and women, among men and men can be removed gradually through egalitarian laws and social practices. The present article, however, seems to contend that the oppressed people's perception of themselves has a key role to play in their empowerment for eliminating such discrimination in and outside their families to effect contemplated change in the society. Administration and Management Review Vol. 21, No. 1, January, 2009, Page 46-57